2009
DOI: 10.1039/b917052a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of supported gold nanoparticles as photocatalysts under ultraviolet and visible light irradiation

Abstract: Gold nanoparticles strongly absorb both visible light and ultraviolet light to drive an oxidation reaction for a synthetic dye, as well as phenol degradation and selective oxidation of benzyl alcohol under UV light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
200
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(207 citation statements)
references
References 25 publications
3
200
0
4
Order By: Relevance
“…Chen et al showed that Au NPs are active for HCHO oxidation to CO 2 under 600-700 nm red light irradiation [13,33,127,128]. Hot electrons can drive also H 2 dissociation on plasmonic Au NPs at room temperature and laser intensity of~2 W cm −2 [129,130].…”
Section: Direct Plasmonic Photocatalysismentioning
confidence: 99%
“…Chen et al showed that Au NPs are active for HCHO oxidation to CO 2 under 600-700 nm red light irradiation [13,33,127,128]. Hot electrons can drive also H 2 dissociation on plasmonic Au NPs at room temperature and laser intensity of~2 W cm −2 [129,130].…”
Section: Direct Plasmonic Photocatalysismentioning
confidence: 99%
“…[147~151] ; 最后, SPR 非辐射弛 豫最终会转化为热, 这种光热效应会导致纳米结构局域 快 速 升 温 , 从 而 为 表 面 化 学 反 应 提 供 必 要 的 活 化 能 [21,152,153] . 这些独特的性质使得金属纳米结构成为一 类极具潜力的光能转化材料 [20] , 现有研究表明金属纳 米结构通过激发 SPR 可以对许多重要的反应都表现出 良好的催化活性, 如光解水反应 [139~143] , 光催化 CO 2 还 原 [154,155] …”
Section: 反应机理unclassified
“…41 It is also apparent that interband transitions dominate the absorption of the metal nanoparticles for wavelengths shorter than 475 nm, 41 a fact that has been recognized in very few cases in the reports on plasmonic photocatalysis. [42][43][44] Thus, quantitative experiments were performed to evaluate the amount of TEMPOL regenerated as a function of the irradiation time by exciting the samples at 450 ± 12 and 530 ± 12 nm. Results are shown in Fig.…”
Section: Tempol ↔ Tempol-h Interconversionmentioning
confidence: 99%